Ok I figured out how to find (FoG)(x) etc. but I am confused on how to find just plain FoG or GoF. For example f(x)=x^2+6 g(x)=sqrt(x-6). How do I find FoG GoF FoF and GoG of these?? Thank you sooo much for your time!!

Results 1 to 3 of 3

- Sep 22nd 2008, 03:29 PM #1

- Joined
- Sep 2008
- Posts
- 1

- Sep 22nd 2008, 04:44 PM #2
$\displaystyle f({\color{red}x}) = {\color{red}x}^2 + 6$

So: $\displaystyle (f \circ g)(x) = f\big({\color{red}g(x)}\big) = {\color{red}g(x)}^2 + 6 = \left({\color{red}\sqrt{x -6}}\right)^2 + 6 = \hdots$

Simply replace x with the function and simplify it.

- Jan 20th 2010, 07:41 PM #3

- Joined
- Jan 2010
- From
- New Zealand
- Posts
- 1

Click on a term to search for related topics.